2015
DOI: 10.1016/j.fertnstert.2015.05.026
|View full text |Cite
|
Sign up to set email alerts
|

Creating a collaborative model of mental health counseling for the future

Abstract: Infertility patients report high levels of anxiety and depressive symptoms, leading to a variety of challenges for the health care team. These include the impact of patient distress on nurses and physicians, patient treatment termination, and potentially lower pregnancy rates. Integrating a mental health professional into the infertility treatment team has the potential to lower distress for patients, support staff, and clinicians, leading to increased patient retention and an easier working environment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 17 publications
0
15
0
1
Order By: Relevance
“…Neste contexto, considerou-se relevante poder ter disponível uma ferramenta que, de um modo mais sistematizado, possibilitasse a abordagem destas motivações, por exemplo, no âmbito do apoio psicológico de casais com indicação para utilização de esperma ou ovócitos de dadores. Atendendo a que o acompanhamento destes casais constitui um importante campo da ação da psicologia no contexto da infertilidade (Domar, 2015), consideramos que o QMRDG constitui um contributo, não apenas para a identificação das motivações, mas também como um possível ponto de partida para a abordagem do tema, estimulando a comunicação entre o casal. Com efeito, a literatura tem sugerido que este deverá ser um tópico introduzido no decorrer do processo de tratamento de reprodução medicamente assistida de forma a que o casal se vá familiarizando com as diferentes perspetivas possíveis e respetivo impacto que a decisão de revelar ou não possa ter para a família e para o desenvolvimento da criança.…”
Section: Discussionunclassified
“…Neste contexto, considerou-se relevante poder ter disponível uma ferramenta que, de um modo mais sistematizado, possibilitasse a abordagem destas motivações, por exemplo, no âmbito do apoio psicológico de casais com indicação para utilização de esperma ou ovócitos de dadores. Atendendo a que o acompanhamento destes casais constitui um importante campo da ação da psicologia no contexto da infertilidade (Domar, 2015), consideramos que o QMRDG constitui um contributo, não apenas para a identificação das motivações, mas também como um possível ponto de partida para a abordagem do tema, estimulando a comunicação entre o casal. Com efeito, a literatura tem sugerido que este deverá ser um tópico introduzido no decorrer do processo de tratamento de reprodução medicamente assistida de forma a que o casal se vá familiarizando com as diferentes perspetivas possíveis e respetivo impacto que a decisão de revelar ou não possa ter para a família e para o desenvolvimento da criança.…”
Section: Discussionunclassified
“…During the evaluation, while screening psychological vulnerability, the professional providing help should monitor the patient's level of distress, emotional state, level of anxiety, depression and stress (Boivin, Takefiman, & Braverman, 2011;Domar, 2015;Van den Broeck et al, 2010;Verhaak et al, 2010). Several infertility distress studies emphasise (Wischmann et al, 2013) that a smaller subgroup can clearly be identified among those who suffer from infertility, these persons are significantly more vulnerable psychologically, especially they are more prone to depression and anxiety.…”
Section: Coping Strategiesmentioning
confidence: 99%
“…Infertility counselling could be conducted by professional helpers such as mental hygienists and nurses who are familiar with psychology, infertility and assisted reproductive treatment. The infertility professional should use the parameters described previously for individuals or couples and should be available during the entire treatment (Covington & Burns, 2006;Domar, 2015;Furman et al, 2010;Stevenson, Hershberger, & Bergh, 2016).…”
Section: Coping Strategiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Infertility affects 15.5% of couples seeking conception and bears significant financial and psychosocial repercussions for both the individuals involved and society in general . Despite a well‐established notion that both nutrition and modifiable lifestyle factors impact female and male reproductive potential, research in this field is not extensive, leaving couples planning pregnancy with few evidence‐based resources to guide preconception diet advice.…”
Section: Introductionmentioning
confidence: 99%